PERAN PEREMPUAN TERHADAP TINGKAT PENGANGGURAN DI KABUPATEN/KOTA PROVINSI BALI - Novriesco Aichiro Halomoan; Putu Ayu Pramitha Purwanti (E-Jurnal Ekonomi Pembangunan, 2023)
This phenomenon shows people's efforts to achieve gender equality in the currenti erai of globalizationi. The ipurpose iof this study iwas toi look at the simultaneous and partial effects of the GEM variables, women's lifei expectancyi, average lengthi of schoolingi for girls, and district/city Labor Force Participation Rate on response rates in districts/cities in Bali Province. This study uses paneil datai which is a icombination of time seriesi datai and cross isection data. This research was conducted within the last ten years, namely 2010-2020 in 9 regencies/cities of Bali Province. The data collected was ithen analyzed iusing panel idata iregression analysis techniques. The results of the study show that simultaneously the Gender Empowerment Index, women's life expectancy, the average length of schooling for women and the Labor Force Participation Rate have a significant effect on the level of stimulation in the districts/cities of the Province of Bali. Meanwhile, the Gender Empowerment Index, women's life expectancy, the average length of schooling for women and the Labor Force Participation Rate partially have a significant negative effect on response rates in the districts/cities of Bali Province. keyword: GEM, women’s life expectancy, average length of schooling for women, labor force participation rate